African Organization for Research and Training in Cancer: position and vision for cancer research on the African Continent. Issue 1 (December 2016) - Ogunbiyi, J.; Stefan, D.; Rebbeck, Timothy
Abstract The African Organization for Research and training in Cancer (AORTIC) bases the following position statements on a critical appraisal of the state on cancer research and cancer care in Africa including information on the availability of data on cancer burden, screening and prevention for cancer in Africa, cancer care personnel, treatment modalities, and access to cancer care.